Modernisation And Reform Of Corporate Law Amidst The Influence Of Globalisation And The Development In Information Technology - Tie, Fatt Hee (Journal of Malaysian and Comparative Law, 2019)
Regulatory measures aimed at reforming corporate law is a daunting and difficult task in view of the dynamic and ever-changing corporate environment. Nevertheless, the process of globalisation and developments in information technology has acted as a catalyst for corporate law reform in a number of jurisdictions. Amidst a meticulous, detailed and comprehensive re-examination of the current law, corporate regulators often face the dilemma of finding an appropriate niche that balances the conflicting needs of economic enterprise and shareholders’ interest.